A case of gastric granular cell tumor. Issue 8 (2nd July 2021) - Kawai, Munenori; Goda, Naoki; Nikaido, Mitsuhiro; Fukuda, Akihisa
Abstract : We herein describe an extremely rare case of gastric granular cell tumor (GCT). The gastric submucosal tumor showed a central tiny depression on the surface with a molar tooth‐like appearance on esophagogastroduodenoscopy. Our case highlights that gastric GCT should be considered as differential diagnosis of gastric submucosal tumors.